2017
DOI: 10.1111/jocn.13803
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of published research literature reviews on nursing and healthcare ageism

Abstract: At this point in time, there is no clear understanding of how widespread and impactful nursing or healthcare ageism is, and what can best be done to prevent or address it. Nurses need to be aware that ageism may be common and impactful, and guard against it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…In HE and particularly in nursing, student nurses are socialised into their new profession with pre-existing ageist beliefs (Neville 2016). Additionally, nurses and clinical placements in older person care may impact negatively on the ageist values of the future workforce (Wilson et al 2017). Consequently, healthcare curricula including nursing which inherently rely on the workplace needs to address ageism and ageist views in clinical practice (Faronbi et al 2017).…”
Section: Socialisation To Ageism In Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…In HE and particularly in nursing, student nurses are socialised into their new profession with pre-existing ageist beliefs (Neville 2016). Additionally, nurses and clinical placements in older person care may impact negatively on the ageist values of the future workforce (Wilson et al 2017). Consequently, healthcare curricula including nursing which inherently rely on the workplace needs to address ageism and ageist views in clinical practice (Faronbi et al 2017).…”
Section: Socialisation To Ageism In Higher Educationmentioning
confidence: 99%
“…Nursing students' HE and clinical practice are important elements of socialisation into their profession; and there is urgent need to influence the understanding of ageing, ageing process, dementia and healthcare provision (Faronbi et al 2017). Appropriate education for nursing students, qualified nurses and other healthcare professionals is necessary for person-centred older people care to be provided and understood by both patient and healthcare provider (Wilson 2017). In the only study with a student nurse sample, Frost et al (2016) suggests the self-administration of ROPE for students to learn to recognise their own ageist practices and recommends early implementation in nursing programmes.…”
Section: Socialisation To Ageism In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ageism is an extensive phenomenon which can be found in many areas of life, including health care. Ageism in health care may have various manifestations, including overtreatment and undertreatment (Ouchida & Lachs, ), lower quality of health care, and limiting older adults' access to certain healthcare services, including rehabilitation care (Forti et al, ; Wilson et al, ). Researcher Becca Levy has found that ageism also results in significant increased healthcare costs as well as increased prevalence of certain medical conditions in people aged 60 and above in the United States (Levy, Slade, Chang, Kannoth, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Scandinavia older people above 80 years are likely to receive help to manage everyday life because of frailty and comorbid diseases, as well as reduced physical and cognitive abilities (3). Ageism in Western societies has in uenced upon health care professionals' attitudes and they often nd it less attractive to work in community-based services; ageism has as well adverse impact upon resource allocation and there are reports of lack of quali ed staff and poor care quality (4)(5)(6). Norwegian research point to undigni ed patient care in nursing homes (7,8).…”
Section: Introductionmentioning
confidence: 99%